2018
DOI: 10.1016/j.joca.2018.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal changes in MR T1ρ/T2 signal of meniscus and its association with cartilage T1p/T2 in ACL-injured patients

Abstract: A significant decrease in PHLAT T1ρ/T2 signal by 2-years suggests potential tissue recovery after ACL-injury. Elevated T1ρ/T2 signal in the PHMED of injured knees at 2-years correlating with knee cartilage T1ρ/T2 signal elevations suggests involvement of the PHMED in subacute cartilage degeneration after ACL-injury and reconstruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 49 publications
0
17
0
Order By: Relevance
“…The qDESS sequence in the present study was optimized to simultaneously generate high-resolution images and quantitative measurements, by combining high spatial resolution with high SNR, in one single, rapid scan. While twice as fast, the resolution and voxel volume of this qDESS sequence (0.18 μL) was over 10x better than the resolution of established quantitative T 2 sequences [7,30]. In a previous study, qDESS has shown high T 2 accuracy compared with multi-echo spin echo sequences, as well as high accuracy for MOAKS measurements compared with conventional spin echo-based sequences, with high intra-and inter-observer reproducibility [16,25].…”
Section: Discussionmentioning
confidence: 80%
“…The qDESS sequence in the present study was optimized to simultaneously generate high-resolution images and quantitative measurements, by combining high spatial resolution with high SNR, in one single, rapid scan. While twice as fast, the resolution and voxel volume of this qDESS sequence (0.18 μL) was over 10x better than the resolution of established quantitative T 2 sequences [7,30]. In a previous study, qDESS has shown high T 2 accuracy compared with multi-echo spin echo sequences, as well as high accuracy for MOAKS measurements compared with conventional spin echo-based sequences, with high intra-and inter-observer reproducibility [16,25].…”
Section: Discussionmentioning
confidence: 80%
“…101 Therefore, with degradation of the cartilage matrix, there is a resultant loss of PG and subsequent measurable increases in T1rho values. [102][103][104][105] T1rho values appear to have a good correlation with histologic assessment of PG. 100,103 One of its main advantages as a modality in evaluating PG distribution is that it does not use contrast, as required with the dGEMRIC technique.…”
Section: T1rho Mappingmentioning
confidence: 76%
“…[102][103][104][105] T1rho values appear to have a good correlation with histologic assessment of PG. 100,103 One of its main advantages as a modality in evaluating PG distribution is that it does not use contrast, as required with the dGEMRIC technique. As with other quantitative MRI techniques, T1rho has been primarily utilized in evaluating knee cartilage and menisci, but more recent work evaluated its utility in the hip, particularly in the context of FAI.…”
Section: T1rho Mappingmentioning
confidence: 76%
“…37 Given the similarities to articular cartilage, T 1 ρ and T 2 mapping allow for detailed evaluation of the meniscus. 38,39 T 2 * has been shown to be significantly longer in degenerative menisci relative to normal meniscal tissue. Intrasubstance degeneration of the meniscus may also be evaluated with dGEMRIC, given its ability to reflect the proteoglycan content of the tissue.…”
Section: Meniscus Imagingmentioning
confidence: 98%